Digital marketing strategy : an integrated approach to online marketing - Kingsnorth, Simon (London ; New York, NY : Kogan Page Limited, 2022)
"Build an effective and practical digital strategy with this bestselling guide to digital marketing, covering everything from automation and analytics to integrating AI. Digital Marketing Strategy is a global bestseller, and a one-stop guide to digital marketing and how to structure and build a more strategic approach. Recommended by the Chartered Institute of Marketing (CIM), a professional marketing body. Now fully updated, this third edition covers the integration of AI in marketing, marketing automation and how to use digital analytical tools, plus new strategies for third-party data and privacy protection. Digital Marketing Strategy will show you how to effectively select, align and manage digital channels and operations, to streamline a winning digital marketing strategy for measurable, optimized results. Learn from real-world case studies including Coca-Cola, MoneySupermarket.com, Bloom & Wild, Airbnb, Adidas, Uber so you can view best-practice examples so you can build your own digital marketing strategy. Accompanying online resources consist of practical implementation guides spanning SEO, paid-search, email, lead-generation, as well as lecture slides and activity sheets. This is an invaluable guide for digital marketing students and entry-level to mid-management professionals"--
Includes bibliographical references and index.
Revised edition of the author's Digital marketing strategy, [2019]
Keywords: Electronic commerce -- Management; Internet marketing; Strategic planning